Long-Term Outcomes of Recipients of Liver Transplants from Living Donors Treated with a Very Low-Calorie Diet - Hannah Wozniak; Sara Naimimohasses; Toru Goto; Gonzalo Sapisochin; Blayne Sayed; Anand Ghanekar; Mark Cattral; Nazia Selzner (Journal of Transplantation, 2024)
The increasing prevalence of steatotic liver disease (SLD) in potential living donors is concerning, as it limits donor’s availability amid rising demand. OPTIFAST very low-calorie diet (VLCD), a meal replacement product, effectively reduces weight and hepatic steatosis before transplantation. However, data on the outcomes of recipients of VLCD-treated donors are lacking. We conducted a single-center, retrospective study on 199 living donor liver transplant recipients at Toronto General Hospital, Canada, between January 2015 and January 2020. We compared the 1-year posttransplant outcomes between recipients who received organs from donors treated with VLCD (N = 34) for either weight loss or steatosis reduction, with those who did not require treatment (N = 165). Our analysis revealed no statistically significant differences in the rates of postoperative complications (23% vs 32.4%, p=0.3) or intensive care unit stays (70.9% vs 70.6%, p=1) between recipients of non-VLCD and VLCD grafts. Following adjusted multivariate logistic regression, receipt of VLCD grafts was not associated with increased hospital length of stay. In addition, one-year mortality did not differ between the two groups (4.2% non-VLCD recipients vs 2.9% VLCD recipients, p=0.6). OPTIFAST VLCD treatment for liver donors demonstrates positive and safe outcomes in recipients, expanding the pool of potential living donors for increased organ availability.